P246 Clinical outcomes of 2012 ECCO/ESPGHAN guidelines in a large cohort of children with ulcerative colitis. (25th January 2019) - Aloi, M; Distante, M; Jaljaa, A; Oliva, S; Isoldi, S; Valitutti, F; Mallardo, S; Cucchiara, S
Abstract: Background: Therapeutic strategies for children with ulcerative colitis (UC) have changed after the publication of the first ECCO/ESPGHAN guidelines on medical management. 1 Our main aim was to evaluate the impact of those recommendations on significant clinical outcomes: colectomy rate, number of acute severe colitis episodes and disease extension, in a large cohort of children with UC over a 3-year follow-up. Methods: Retrospective analysis of children diagnosed with UC between 2006 and 2011 (Group 1) and 2012 and 2016 (Group 2) and identified at our department database. Records were reviewed for disease location and severity, laboratory and endoscopic findings, treatments and rate of surgery, hospitalisation and disease extension at the diagnosis and every year. Results: One hundred fifty-seven patients were identified (45% F; median age 11, IQR 1, 2–16.7; 80 Group 1, 77 Group 2). A significant higher use of infliximab was found at 1 and 2 years in Group 2 (18% vs. 6%, p = 0.02 and 25% vs. 11%, p = 0.04, respectively), while no significant differences were found at 3 years (27% vs. 17%, p = 0.30). Immunomodulator use was significantly higher in Group 1 at the end of follow-up ( p = 0.001). Fourteen patients (9%) needed surgery at follow-up, with no significant differences between eras (10% Group 1, 8% Group 2, p = 0.83). The number of episodes of acute severe colitis decreased from 23% to 10% ( p = 0.05) between the first and the second period, while no significant differences were found for disease extension ( p = 0.83). Conclusions: After 2012, a significant reduction of episodes of acute severe colitis and an increased early use of infliximab have been observed in this large cohort of children with UC. Nevertheless, the rate of colectomy remained unchanged. Reference 1. Turner D, Levine A, Escher JC, et al . Management of pediatric ulcerative colitis: joint ECCO and ESPGHAN evidence-based consensus guidelines. J Pediatr Gastroenterol Nutr 2012;55:340–61.